2016
DOI: 10.1117/1.jbo.21.11.110501
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast optical property map generation using lookup tables

Abstract: Imaging technologies working in the spatial frequency domain are becoming increasingly popular for generating wide-field maps of optical properties, enabling rapid analysis of tissue parameters. While acquisition methods have become faster and are now performing in real-time, processing methods remain slow, precluding real-time display of information. We present solutions that rapidly solve the inverse problem for extracting optical properties by use of advanced lookup tables (LUTs). We present methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 12 publications
(18 reference statements)
0
50
0
Order By: Relevance
“…Utilizing a faster acquisition technique such as single snapshot [23] or a faster processing technique such as the look up table (LUT) model recently proposed by Angelo et. al [24] could reduce the overall quantification time and provide results in the clinic. This near real-time feedback would be particularly useful for monitoring light-based therapies such as laser or photodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing a faster acquisition technique such as single snapshot [23] or a faster processing technique such as the look up table (LUT) model recently proposed by Angelo et. al [24] could reduce the overall quantification time and provide results in the clinic. This near real-time feedback would be particularly useful for monitoring light-based therapies such as laser or photodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Demodulation time is currently estimated at 100 ms, though this processing is currently being done in MATLAB and could certainly be optimized for real-time feedback. While the current processing time to invert diffuse reflectance maps to optical properties is typically on the order of 1 second, we recently demonstrated that this inversion time could be reduced significantly to approximately 10 ms [31]. Altogether this work lays the foundation of real-time quantitative optical imaging through an endoscope and its clinical translation, potentially enabling endoscopic implementation of current quantitative, widefield techniques [32][33][34].…”
Section: Discussionmentioning
confidence: 95%
“…However, with model based inversion methods, fitting time is a limitation. While look-up-table approaches could provide a substantial improvement, a direct calculation of optical properties from an empirically fitted function has demonstrated faster inversion times without the need for a look-up routine (Angelo et al 2016). A classification model based on raw multi-spectral reflectance over multiple spatial frequencies may overcome the computational barrier.…”
Section: Discussionmentioning
confidence: 99%